2008
DOI: 10.1162/jocn.2008.20106
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic Metaplasticity in the Human Somatosensory Cortex

Abstract: Long-term potentiation (LTP) and long-term depression (LTD) are regulated by homeostatic control mechanisms to maintain synaptic strength in a physiological range. Although homeostatic metaplasticity has been demonstrated in the human motor cortex, little is known to which extent it operates in other cortical areas and how it links to behavior. Here we tested homeostatic interactions between two stimulation protocols -- paired associative stimulation (PAS) followed by peripheral high-frequency stimulation (pHF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 54 publications
3
37
2
Order By: Relevance
“…For example, PAS N20 - 2.5 to S1 paired with pHFS facilitated P25 amplitudes and improved tactile spatial acuity as measured with the GOT task (Werhahn, Mortensen, Van Boven, Zeuner, & Cohen, 2002) while PAS N20 - 2.5 paired with pHFS inhibited P25 components and decreased tactile acuity. Unlike previous studies, PAS alone had no effect perhaps explained by slight differences in stimulation protocols (150% RMT, 225 pairs at a faster rate of 0.25Hz) (Bliem, Muller-Dahlhaus, Dinse, & Ziemann, 2008). …”
Section: Transcranial Magnetic Stimulation (Tms)contrasting
confidence: 70%
“…For example, PAS N20 - 2.5 to S1 paired with pHFS facilitated P25 amplitudes and improved tactile spatial acuity as measured with the GOT task (Werhahn, Mortensen, Van Boven, Zeuner, & Cohen, 2002) while PAS N20 - 2.5 paired with pHFS inhibited P25 components and decreased tactile acuity. Unlike previous studies, PAS alone had no effect perhaps explained by slight differences in stimulation protocols (150% RMT, 225 pairs at a faster rate of 0.25Hz) (Bliem, Muller-Dahlhaus, Dinse, & Ziemann, 2008). …”
Section: Transcranial Magnetic Stimulation (Tms)contrasting
confidence: 70%
“…(For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.) evidence for homeostatic plasticity in primary somatosensory cortex [85,86]. Both studies used an NTBS prime preceding a highfrequency tactile stimulation (HFS) protocol of the contralateral hand in order to demonstrate a homeostatic response in the somatosensory cortex.…”
Section: Intercortical Homeostatic Plasticitymentioning
confidence: 99%
“…For instance, animal experiments demonstrated that depending on the degree of neuronal depolarization the same tetanic stimulation protocol induced either LTP or LTD [26]. In healthy subjects, it has been shown that metaplasticity operates not only in M1 but also in S1 and that it influences corticospinal excitability as well as somatosensory skills [27] 2 SAI before and after 1 Hz rTMS over S1 and M1 is demonstrated for CD patients. Also, SAI of controls before and after S1 rTMS is shown.…”
Section: Discussionmentioning
confidence: 99%